2019
DOI: 10.1108/rpj-07-2019-0187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D printed mouthpieces for musical instruments

Abstract: Purpose The purpose of this study is the evaluation of advantages and criticalities related to the application of addtive manufacturing (AM) to the production of parts for musical instruments. A comparison between traditional manufacturing and AM based on different aspects is carried out. Design/methodology/approach A set of mouthpieces produced through different AM techniques has been designed, manufactured and evaluated using an end-user satisfaction-oriented approach. A musician has been tasked to play th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In another study, trombone mouth pieces were designed, manufactured and statistically evaluated based on various end user requirements like sound quality, buying cost, customization and personal symbol, mouth and lips comfort, ease of storing the mouthpiece, loudness, etc. [17]. They have found that in comparison with a metallic mouthpiece, SLA-printed mouthpieces fared better design solutions.…”
Section: Personalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, trombone mouth pieces were designed, manufactured and statistically evaluated based on various end user requirements like sound quality, buying cost, customization and personal symbol, mouth and lips comfort, ease of storing the mouthpiece, loudness, etc. [17]. They have found that in comparison with a metallic mouthpiece, SLA-printed mouthpieces fared better design solutions.…”
Section: Personalizationmentioning
confidence: 99%
“…A trombone mouthpiece reported in [17] was developed using SLA. They focussed on the different AM technologies to investigate the change in geometry, material on the sound characteristics of the instrument.…”
Section: Stereolithography (Sla)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additive manufacturing can further be used in the jewelry [5] and construction industries [6]. Niche applications include mouthpieces for musical instruments [7] or textiles for clothing [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several contributions in the literature focus on the design and manufacturing of woodwind mouthpieces for saxophone or clarinet [4,5,8,14]. The source [15] focuses on the production of brass instruments such as the trombone's mouthpiece through AM. Indeed, this work can be seen as a continuation of the research carried out in [15].…”
Section: Introductionmentioning
confidence: 99%